2002
DOI: 10.1152/jn.00395.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spectrotemporal Receptive Fields in the Lemniscal Auditory Thalamus and Cortex

Abstract: Receptive fields have been characterized independently in the lemniscal auditory thalamus and cortex, usually with spectrotemporally simple sounds tailored to a specific task. No studies have employed naturalistic stimuli to investigate the thalamocortical transformation in temporal, spectral, and aural domains simultaneously and under identical conditions. We recorded simultaneously in the ventral division of the medial geniculate body (MGBv) and in primary auditory cortex (AI) of the ketamine-anesthetized ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
348
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(393 citation statements)
references
References 67 publications
45
348
0
Order By: Relevance
“…In anesthetized cats, frequency bandwidths have been measured in most stages of the ascending pathway. It has been shown that average frequency bandwidths increase from about 1/4th octave in the auditory nerve to about 1 octave in primary auditory cortex (A1) (Miller et al 2002;Moshitch et al 2006;Pickles 1979;Ramachandran et al 1999). A similar trend was observed in a number of primate studies (see Table 1).…”
mentioning
confidence: 54%
“…In anesthetized cats, frequency bandwidths have been measured in most stages of the ascending pathway. It has been shown that average frequency bandwidths increase from about 1/4th octave in the auditory nerve to about 1 octave in primary auditory cortex (A1) (Miller et al 2002;Moshitch et al 2006;Pickles 1979;Ramachandran et al 1999). A similar trend was observed in a number of primate studies (see Table 1).…”
mentioning
confidence: 54%
“…Such processing is already under study in auditory neurophysiology (Kowalski et al, 1996a,b;Depireux et al, 2001;Miller et al, 2001Miller et al, , 2002Escabí and Schreiner, 2002) and psychoacoustics (Chi et al, 1999), and is also being investigated for various signal-processing tasks, including audio coding (Atlas and Shamma, 2003;Klein et al, 2003) and speech recognition (Hermmansky, 1999;Nadeu et al, 2001;Kleinschmidt and Gelbart, 2002;Kleinschmidt, 2002).…”
Section: The Linear Processing Of Spectrotemporal Modulation Frequenciesmentioning
confidence: 99%
“…Each spectrotemporal modulation frequency is the conjunction of a spectral and a temporal modulation frequency; the higher the spectral modulation frequency, the sharper the spectral feature (e.g., sharp peaks or edges in the spectrum), and the higher the temporal modulation frequency, the more abruptly that feature changes in time. As a population, the strongest phase-locked response in central auditory neurons occurs over a select range of low spectral and temporal modulation frequencies (Rees and Moller, 1983;Shamma et al, 1995;Schreiner and Calhoun, 1995;Kowalski et al, 1996a;Depireux et al, 2001;Sen et al, 2001;Miller et al, 2002;Escabí and Schreiner, 2002). Not surprisingly, the most fruitful stimuli have had spectrotemporal modulation frequencies concentrated within this range.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tuning curves from cat cochlear nucleus neurons were predicted from the neuron's response to cosine noise (Bilsen et al 1975;ten Kate & van Bekkum 1988). More recently, cat auditory cortical neurons have been shown to respond selectively and systematically to acoustic stimuli with sinusoidal spectral envelopes (Schreiner & Calhoun 1994;Calhoun and Schreiner;Miller et al, 2002). Studies in ferret AI find that ripple responses allow predictions of responses to pure tones and to spectrally complex natural sounds Versnel and Shamma 1998;Klein et al, 2000) suggesting that AI neurons analyze the shape of acoustic spectra in a substantially linear manner.…”
Section: Physiology Of Ripple Spectramentioning
confidence: 99%
“…Auditory gratings or ripple spectra, i.e. broad-band stimuli with sinusoidal spectral envelopes similar to the structure of vowels, have been used to characterize spectral integration properties of central auditory neurons (e.g., Schreiner and Calhoun, 1994;Shamma et al, 1995;Klein et al, 2000;Miller et al, 2002;Escabi and Schreiner, 2002). Cat and ferret cortical neurons respond preferentially to a narrow range of formant ratios or spectral envelope frequencies (Calhoun and Schreiner, 1998;Klein et al, 2000;Kowalski et al, 1996;Schreiner and Calhoun, 1994;Shamma et al, 1995).…”
Section: Introductionmentioning
confidence: 99%